Advances in the practice of microsurgery: focusing on free anterolateral thigh perforator flap (Faculty of Medicine Universitas Indonesia, 2007)
The purpose of this paper was to discuss an overview of the current clinical practice of microsurgery with a specific use of free anterolateral flap as one of the commonest flaps used in reconstructive surgery. A systematic review was performed through all English publication that goes to Pubmed during the period of 1997 to 2006 using keywords: